Sosialisasi Penggunaan E-Commerce Dalam Mengembangkan Bisnis Di Era Digital Terhadap Siswa-Siswi Ma Annur Pagar Jati Bengkulu Tengah - Setiawan, Naldi; Subhi, Ramadan; Herlina, Yeni (Jurnal Dehasen Mengabdi, 2024)
The development of digital technology has brought significant changes in various aspects of life, including the business sector. E-commerce is one of the important innovations in the business world that facilitates online transactions. This article aims to examine the effectiveness of socialization on the use of e-commerce in business development for students of MA Annur Pagar Jati, Central Bengkulu. This research uses the Participatory Action Research (PAR) method.. Data were collected through observation and discussion interviews with students of MA Annur Pagar Jati. The results showed that students' understanding of e-commerce increased after the socialization. They better understand the basic concepts of e-commerce, the benefits in business development, and how to use it. This socialization also fosters interest in entrepreneurship among students. Recommendations are given to increase the intensity and quality of socialization to prepare the younger generation to face the challenges of the digital era.